2023
DOI: 10.3390/pathogens12060765
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the Relevance of the Oral Cavity as a Staphylococcus aureus Colonization Site and Potential Source of Antimicrobial Resistance

Abstract: Staphylococcus aureus is both a human commensal and a pathogen, that causes serious nosocomial and community-acquired infections. Despite nostrils being considered its preferred host habitat, the oral cavity has been demonstrated to be an ideal starting point for auto-infection and transmission. The antibiotic resistance assessment of S. aureus is a priority and is often reported in clinical settings. This study aimed to explore the prevalence and antimicrobial susceptibility of S. aureus in the oral and nasal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…16 In another study, Campos et al reported the prevalence of S. aureus in the oral and nasal cavities, showing 13.9% from the nasal cavity, 12.0% from the oral cavity, and 9.9% from both sites in healthy volunteers (average age: 21.83 ± 3.53 years). 17 Vanzato Palazzo et al reported that the prevalence of S. aureus and MRSA was 47.6% and 4.1%, respectively, in the saliva of 340 healthcare workers. 35 Petti et al also reported that the prevalence of S. aureus and MRSA was 8.9% and 1.9%, respectively, in oral swabs of 157 dental students.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 In another study, Campos et al reported the prevalence of S. aureus in the oral and nasal cavities, showing 13.9% from the nasal cavity, 12.0% from the oral cavity, and 9.9% from both sites in healthy volunteers (average age: 21.83 ± 3.53 years). 17 Vanzato Palazzo et al reported that the prevalence of S. aureus and MRSA was 47.6% and 4.1%, respectively, in the saliva of 340 healthcare workers. 35 Petti et al also reported that the prevalence of S. aureus and MRSA was 8.9% and 1.9%, respectively, in oral swabs of 157 dental students.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13] In addition, the emergence of methicillin-resistant S. aureus (MRSA) has become more serious for chemotherapeutic treatment. 14,15 S. aureus, including MRSA, is also isolated from the oral cavity 16,17 and is a causative pathogen for aspiration pneumonia. [18][19][20] Aspiration pneumonia is caused by aspiration of food or saliva, which allows bacteria to enter the respiratory system and cause infection.…”
Section: Introductionmentioning
confidence: 99%